Effect of the Processing Conditions on the Supercritical Extraction and Impregnation of Rosemary Essential Oil in Linear Low-Density Polyethylene Films - Galotto-Lopez, M; Rojas-Sepulveda, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The supercritical fluid extraction of essential oil from rosemary leaves and its subsequent impregnation in linear low-density polyethylene (LLDPE) films were studied. The effects of temperature (318 and 338 K), pressure (15 and 25 MPa) and rosemary particle size (0.9 and 0.15 mm) on the extraction yield were investigated. Impregnation assays were developed at two different values of pressure (12 and 20 MPa), temperature (308 and 328 K), and impregnation time (1 and 5 h). The extraction yield of rosemary essential oil was increased by increasing pressure and decreasing particle size and temperature. ANOVA results showed that temperature, pressure, and time significantly impacted the essential oil impregnation yield in LLDPE films. The maximum impregnation yield (1.87 wt. %) was obtained at 12 MPa, 328 K, and 5 h. The antioxidant activity and the physical-mechanical properties of impregnated films were analyzed. The IC50 values for all the impregnated LLDPE samples were close to the IC50 value of the extract showing that the impregnated films have a significant antioxidant activity. © 2022 by the authors.
Keywords: essential oil; rosemary; supercritical impregnation; LLDPE; antioxidant activity